Multimodal Discourse Features in Selected Nigerian Political Cartoons - Adeagbo, Esther Olajumoke; Oyindamola, Abiade Ayomide (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Political cartoons in Nigerian society serve as tools for political commentary and social critique. This research investigates the socio-political impact of visual and linguistic strategies in selected Nigerian political cartoons, addressing a significant gap in the existing literature concerning the role of visual media in political discourse. Despite the prevalent use of political cartoons in Nigerian media, there has been limited scholarly attention to how these cartoons utilise visual and linguistic elements to critique socio-political disputes. This study aims to bridge this gap by employing Kress and van Leeuwen’s Grammar of Visual Design and Roland Barthes’ Semiotic Theory to analyse seven selected political cartoons. The study’s primary aim is to explore how these cartoons communicate complex political realities and influence public perception. The objectives include identifying the visual and linguistic strategies used in the cartoons, examining the socio-political issues they address, and evaluating their impact on public discourse. The findings reveal that Nigerian political cartoons employ a sophisticated blend of visual and linguistic strategies to convey powerful socio-political messages. The analysis demonstrates that these cartoons effectively highlight issues such as corruption, economic hardship, political neglect, and the disparity between the ruling elites and the suffering masses. The study also found that these cartoons effectively depict the disparity between the ruling elites and the suffering masses, employing salience, framing, modality, denotation, connotation, and myth to engage and challenge public perception. The research underscores the significance of political cartoons as tools for socio-political engagement and discourse, demonstrating their role in reflecting and shaping public opinion on critical national issues. In conclusion, this study underscores the importance of political cartoons as a medium for socio-political engagement and discourse in Nigeria. It highlights the critical role of visual semiotics in political commentary and the necessity for further research into the impact of visual media on public opinion and political accountability.